Patient specific modeling of palpation‐based prostate cancer diagnosis: effects of pelvic cavity anatomy and intrabladder pressure. (19th August 2015) - Palacio‐Torralba, Javier; Jiménez Aguilar, Elizabeth; Good, Daniel W.; Hammer, Steven; McNeill, S. Alan; Stewart, Grant D.; Reuben, Robert L.; Chen, Yuhang
Summary: Computational modeling has become a successful tool for scientific advances including understanding the behavior of biological and biomedical systems as well as improving clinical practice. In most cases, only general models are used without taking into account patient‐specific features. However, patient specificity has proven to be crucial in guiding clinical practice because of disastrous consequences that can arise should the model be inaccurate. This paper proposes a framework for the computational modeling applied to the example of the male pelvic cavity for the purpose of prostate cancer diagnostics using palpation. The effects of patient specific structural features on palpation response are studied in three selected patients with very different pathophysiological conditions whose pelvic cavities are reconstructed from MRI scans. In particular, the role of intrabladder pressure in the outcome of digital rectal examination is investigated with the objective of providing guidelines to practitioners to enhance the effectiveness of diagnosis. Furthermore, the presence of the pelvic bone in the model is assessed to determine the pathophysiological conditions in which it has to be modeled. The conclusions and suggestions of this work have potential use not only in clinical practice and also for biomechanical modeling where structural patient‐specificity needs to be considered. © 2015 The Authors. International Journal for Numerical Methods in Biomedical Engineering published by John Wiley & Sons Ltd. Abstract : In this study patient‐specific modeling is investigated in the framework of male pelvic cavity modeling for the purpose of prostate cancer diagnosis. It is found that anatomy of pelvic cavity plays an important role in determining the outcome of instrumented digital rectal examination. Variation of intrabladder pressure and the presence of pelvic bone are also explored, and the results show that taking into account those patient‐specific factors would greatly improve the effectiveness of clinical diagnosis of prostate cancer using palpation.